2009
DOI: 10.1007/s10753-009-9168-5
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Characterization of Ozone-Induced Pulmonary Inflammation in the Cynomolgus Monkey

Abstract: We investigated the cellular and molecular effects of ozone exposure in Cynomolgus monkeys. Thirty-six Cynomolgus monkeys were exposed to single or repeat ozone challenge. Pulmonary inflammation was assessed using bronchoalveolar lavage fluid (BAL) and histology. Gene expression profiling in lung and blood was performed. Ozone challenge evoked BAL cellular inflammation and increases in total protein, alkaline phosphatase and cytokines. Lung histology revealed cellular inflammation and epithelial necrosis. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Consistent with the reported inflammatory effects of ozone in rhesus monkeys, a recent investigation in adult cynomolgus monkeys also shows that PMNs are the major leukocyte population recruited into the lung following acute ozone exposure (1 ppm/6 h) (23). In the current study, we found that airways inflammation in 6-mo-old monkeys immediately following 5 mo of episodic exposure at 0.5 ppm/8 h is eosinophilic in phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the reported inflammatory effects of ozone in rhesus monkeys, a recent investigation in adult cynomolgus monkeys also shows that PMNs are the major leukocyte population recruited into the lung following acute ozone exposure (1 ppm/6 h) (23). In the current study, we found that airways inflammation in 6-mo-old monkeys immediately following 5 mo of episodic exposure at 0.5 ppm/8 h is eosinophilic in phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…We have shown that ongoing oxidative damage and inflammation are important in the pathogenesis of progressive pulmonary disease in rodents, and have also documented involvement of the TGF-beta pathway in radiation-induced pulmonary fibrosis in the rat model [ 27 ]. Gene expression studies of the response of primate lungs to ozone-induced oxidative injury also show not only an inflammatory response, with elevations of interleukins 6, 8 and 10, but also a matrix remodeling response, including 3- to 5-fold elevations of matrix metalloproteinase I, metallothionein, and tenascin [ 66 ]. Involvement of TGF beta and matrix remodeling pathways may provide additional preventive or therapeutic targets, in addition to oxidative damage pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We found that ozone-induced increases in BAL protein were correlated with elevated levels of lipocalin 24p3, an acute phase protein and marker of oxidative stress (Roudkenar et al, 2007; Sunil et al, 2007). Lipocalin 24p3 has been detected in the lung after exposure of rodents to endotoxin or particulate matter, as well as in sputum from patients with chronic obstructive pulmonary disease, and in blood from Cynomolgus monkeys exposed to ozone (Andre et al, 2006; Hicks et al, 2010; Keatings et al, 1997; Sunil et al, 2007; Sunil et al, 2009). Our findings that lipocalin 24p3 is increased in the lung after ozone are novel, and suggest that it may be a sensitive marker of acute oxidant-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%